Tiara[6]arenes. Issue 8 (3rd August 2021) - Chao, Yang; Sue, Andrew C.-H.
ABSTRACT: Herein we report the successful synthesis and isolation of tiara[6]arene, a constitutional isomer of calix[6]arene consisting of six phenol units linked by para -substituted methylene bridges, from an isomeric mixture of asymmetrically substituted pillar[6]arene intermediates. Similar to its pentameric analogue, tiara[6]arene displays high conformational freedom in solution and rich polymorphism in the solid state. The establishment of the tiara[ n ]arene family ( n = 5 and 6) further expands the scope of macrocyclic chemistry. Graphical Abstract: uf0001